2013
DOI: 10.1021/jp4042292
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cu in Degrading Adsorption of CO on the PtnCu Clusters

Abstract: The platinum copper alloy nanocrystals (NCs) have generated much interest because of their wide applications in fuel cells due primarily to their good catalytic performance and to decreasing sensitivity toward CO poisoning. The exact atomic-level morphology of platinum copper alloy NCs is still not clear in the literature, and research to understanding the poisoning mechanism is still insufficient to date. In this article, we report on density functional calculations of small PtnCu clusters and their adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…From this observation, we expect smaller electrostatic interactions of the HOMO orbitals, degrading the adsorption of CH 3 . 44 On the other hand Ni 12 possesses more localization on the cluster surface. We also attribute this property to the low coordination of Ni 10 (ECN = 4.71) in comparison to Ni 12 (ECN = 5.47).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…From this observation, we expect smaller electrostatic interactions of the HOMO orbitals, degrading the adsorption of CH 3 . 44 On the other hand Ni 12 possesses more localization on the cluster surface. We also attribute this property to the low coordination of Ni 10 (ECN = 4.71) in comparison to Ni 12 (ECN = 5.47).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Recently, the importance of electronic structure effects for CO tolerance enhancement was theoretically characterized for small Pt n Cu (n ≤ 7) clusters and for alloy Pt-Ti clusters up to sizes of 201 atoms. 29,30 The effect of composition on the electronic structure in small clusters and the consequences for the CO adsorption energy have been illustrated for 13-atom Pt-Au clusters and demonstrated the importance of the local environment of the transition metal atom with the CO adsorbed. 31 The enhancement of the CO tolerance in comparison with bulk alloys was demonstrated for a number of Pt-Me (Me = Mo, Nb, Ru, Sn, and Ag) clusters and nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…HRTEM image (Fig. 5f) of PtCo/rGO catalyst with a Pt:Co ratio of 1:9 shows the 'd' spacing's of 2.23 and 2.19 Aº corresponding to (111) and ( 220) planes of PtCo. The decrease in 'd'values of PtCo alloy in comparison to that of pure Pt ( 111) is explained by the substtution of cobalt for Pt thus confirming the formation of PtCo alloy and that these results are in consistent with the XRD results.…”
Section: Morphology Of the As-synthesized Electrocatalystsmentioning
confidence: 99%
“…It has recently been found that Cu also exhibit water activation and other related reaction, such as the electro-reduction of CO2 [110]. Therefore, the alloy of Pt with Cu are considered to be effective electrocatalysts catalysts which are resistant to COads and similar intermediates [111]. Therefore, PtCu alloy catalysts supported on different support materials including multiwalled carbon nanotubes, carbon black and rGO etc have recently attracted a great attention for MOR both in acidic as well as in alkaline medium [96,99,110,[112][113][114][115][116][117] etc.…”
Section: Electro-oxidation Of Methanol Using Ptcu Alloy Nanoparticles Supported On Nitrogen Doped Rgomentioning
confidence: 99%
See 1 more Smart Citation